PENGARUH INFLASI, SUKU BUNGA SBI, TARIF PAJAK DAN PROFITABILITAS TERHADAP STRUKTUR MODAL (Studi Kasus Pada Perusahaan Manufaktur Subsektor Logam Dan Sejenisnya Yang Terdaftar Di Bursa Efek Indonesia Selama Periode 2014-2017) - Alfiananda Dwi Yulianto; Jeni Susyanti; M. Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACKIn this study the author will discussion of Inflation, BI Rate, Tax Rate and Profitability that can affect the Company's Capital Structure. The purpose of this study is (1) To determine the effect of inflation on capital structure (2) To determine the effect of SBI interest rates on capital structure (3) To determine the effect of tax rates on capital structure (4) To determine the effect of profitability on capital structure.This type of research is Causal Associative. this study took samples from the population using purposive sampling techniques. Case study of lofam sub-sector manufacturing companies and the like for the period 2014-2017. Using two types of variables, namely Dependent Variables and Independent Variables. The results of this study are (1) Inflation has no significant effect on capital structure (2) BI Rate does not affect the capital structure (3) Tax rates have a significant effect on capital structure (4) Profitability does not affect the capital structure.Keywords: Inflation, BI Rate, Tax Rate, Profitability, Capital Structure.